Bioefficacy, phytotoxicity, safety to natural enemies and residue dynamics of imidacloprid 70 WG in okra (Abelmoschus esculenta (L) Moench) under open field conditions. (May 2015) - Karthik, P.; Venugopal, Sheela; Datchina Murthy, K.; Lokesh, S.; Karthik, G.; Sharmila, U.; Paramasivam, M.; Senguttuvan, K.; Gunasekaran, K.; Kuttalam, S.
Abstract: Sucking pests are a major menace and cause considerable damage to okra cultivation in India. Field experiments were carried out to evaluate the bioefficacy, phytotoxicity, safety and residue dynamics of imidacloprid in okra ( Abelmoschus esculenta (L.) Moench). Out of the four doses tested viz ., imidacloprid 70 WG at 17, 21, 24.5 and 35 g a.i ha −1, the 24.5 g a.i ha −1 dose was equally effective in controlling sucking pests viz., aphids, Aphis gossypii (Glover), leafhoppers, Amrasca biguttula biguttula Ishida and thrips, Thrips tabaci Lindeman as the highest dose of 35 g a.i. ha −1 under open field conditions, reducing pest populations by >80% when compared to untreated controls after two rounds of foliar application at an interval of 15 days. The chemical did not cause any phytotoxic symptoms even at 49 g a.i ha −1 . It was also found to be safer to the natural enemies (spiders and coccinellids) prevailing in the okra ecosystem when compared with the higher dose of 35 g a.i. ha −1 . Initial deposits of imidacloprid 70 WG at 24.5 and 49 g a.i. ha −1 in okra fruits were 0.15 and 0.26 μg g −1, respectively, and the residues fell to the Below Detection Limit (BDL) of 0.01 μg g −1 five days after application at both the doses. Imidacloprid residue dissipation followed first order kinetics with half-lives ranging between 1.04 and 1.13 days for the above two doses, respectively. The residues dissipated to below the MRL of 0.7 μg g −1 on the same day. These findings can be utilized in deciding the spray schedule and for safety evaluation of imidacloprid in okra crops. Highlights: Imidacloprid 70 WG at 24.5 g a.i ha −1 was effective in controlling sucking pests of okra. It was found to be safer on okra and also comparatively safer to natural enemies such as spiders and coccinellids. Half-lives were 1.04 and 1.13 days for imidacloprid at 24.5 and 49 g a.i ha −1, respectively. Residues dissipated below MRL values (0.7 μg g −1 ) in one day.